2017
DOI: 10.4172/2155-9600.1000575
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Polyphenol Content of Newly Released Varieties of Wheat during Different Processing Methods

Abstract: Background: Wheat (Triticum aestivum) is the most important food crop in India and most important cereal grain. It is widely consumed in northern India. It is the leading source of all the macronutrients like proteins (especially vegetable protein), energy and carbohydrates and micronutrients like minerals (iron, calcium, zinc, potassium etc.) and B vitamins. It is currently second to rice in terms of total production (tonnes) as the main human food crop. The wheat flour besides various nutrients also contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The results showed that the phytic acid content of composite flour (191.05 mg) differs significantly from that of barley husk (3.66 mg) Parmar and Dahiya (2013) analyzed the phytic acid in wheat flour ( between 167.18 to 241.63 mg), which was similar to the result of the present study. Perea et al (2019) measured the phytic acid level in barley husk and found it to be 2.32 mg, which was higher than the value reported in this study.…”
Section: Antinutrientssupporting
confidence: 90%
“…The results showed that the phytic acid content of composite flour (191.05 mg) differs significantly from that of barley husk (3.66 mg) Parmar and Dahiya (2013) analyzed the phytic acid in wheat flour ( between 167.18 to 241.63 mg), which was similar to the result of the present study. Perea et al (2019) measured the phytic acid level in barley husk and found it to be 2.32 mg, which was higher than the value reported in this study.…”
Section: Antinutrientssupporting
confidence: 90%
“…Rakhi and Puni (2013) indicated that the percentage of phytic acid in varieties studied were (206.71, 240.10) mg/100gm, and a decreased after germination to (33.21, 38.27) mg/100gm respectively. Parmar and Dahiya (2015) showed that phytic acid content were (234.15, 238.06, 253.9) mg/100gm in bread wheat cultivars and decrease to (167.18, 183.48, 205.11) mg/100gm after germination.…”
Section: Mineral Elements Determinationmentioning
confidence: 99%
“…The phenolic content is usually related to different factors other than the microbial composition. Although cereal grains are a good source of bioactive compounds, their level and activity are affected by cereal species and varieties, the nature of the antioxidants, the milling process producing flours with different degrees of refining, and food processing [ 1 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. In detail, durum wheat has higher phenol and antioxidant activity than soft wheat [ 76 , 86 ]; similarly, whole flour and bread more than the refined [ 87 , 88 , 89 , 90 ], since phenolic compounds are mostly present in the outer layers of the grain that are usually removed by the milling industries [ 91 ].…”
Section: Discussionmentioning
confidence: 99%